IMPROVING STUDENTS VOCABULARY MEMORIZATION BY USING THE LOUD HOUSE CARTOON FOR FIFTH GRADE STUDENTS - Nur Amanda, Tria; Nadrah; Pebri Prandika Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the vocabulary memorization of fifth-grade students at SDN 071 Bengkulu Utara through the use of The Loud House cartoon as an audio-visual learning medium. The study was motivated by students' low ability to memorize English vocabulary, as indicated by difficulties in understanding word meanings, recalling previously learned vocabulary, and low learning motivation due to the use of less engaging teaching methods. This research employed Classroom Action Research (CAR) adapted from the model proposed by Arikunto, Suhardjono, and Supardi (2010), consisting of two cycles: planning, acting, observing, and reflecting. The participants were 19 fifth-grade students of SDN 071 Bengkulu Utara. Data were collected through vocabulary tests, classroom observations, and documentation, and were analyzed descriptively by comparing the results of each cycle. The findings revealed that the implementation of The Loud House cartoon effectively improved students' vocabulary memorization. The students' mean score increased from 64.21 in Cycle I to 79.79 in Cycle II, showing an improvement of 15.58 points. In addition, 16 out of 19 students (84.21%) successfully achieved the Minimum Mastery Criterion (KKM) of 75. Classroom observations also indicated that students became more active, enthusiastic, and confident during the learning process. Therefore, the use of The Loud House cartoon is an effective alternative audio-visual learning medium for improving English vocabulary memorization among elementary school students.